Die Tiertheologie und die Schöpfungstheologie - Herdramm, Henrike

Nachhaltigkeit durch Daten im MBSE: Einblick in die Entwicklung eines Modell-Empfehlungssystems - Tissen, Denis; Tschirner, Christian; Koldewey, Christian; Dumitrescu, Roman (Tag des Systems Engineering)

Uncool cowboys in low-low-land? Public perception and aesthetics of the German country music scene. - Jacke, Christoph; Kirschlager, Nils (Beyond Style and Genre. Aesthetic Concepts in Popular Culture.)

A process-model for tailoring prototyping of cyber-physical systems - Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman

Hypernetworks: Cluster Synchronization Is a Higher-Order Effect - von der Gracht, Sören; Nijholt, Eddie; Rink, Bob (SIAM Journal on Applied Mathematics)
Many networked systems are governed by non-pairwise interactions between nodes. The resulting higher-order interaction structure can then be encoded by means of a hypernetwork. In this paper we consider dynamical systems on hypernetworks by defining a class of admissible maps for every such hypernetwork. We explain how to classify robust cluster synchronization patterns on hypernetworks by finding balanced partitions, and we generalize the concept of a graph fibration to the hypernetwork context. We also show that robust synchronization patterns are only fully determined by polynomial admissible maps of high order. This means that, unlike in dyadic networks, cluster synchronization on hypernetworks is a higher-order, i.e., nonlinear, effect. We give a formula, in terms of the order of the hypernetwork, for the degree of the polynomial admissible maps that determine robust synchronization patterns. We also demonstrate that this degree is optimal by investigating a class of examples. We conclude by demonstrating how this effect may cause remarkable synchrony breaking bifurcations that occur at high polynomial degree.
Keywords: Applied Mathematics

Lawrence Grossberg (2019): Pessimismus des Willens, Optimismus des Verstands. Schlussstriche und Neuanfänge. Hrsg. von Roman Horak. Wien und Berlin: Turia + Kant; Roman Horak (2019): Jenseits der Kulturwissenschaften. Beiträge zu Cultural Studies, Popular- und Massenkultur. Wien: Löcker; Jürgen Mittelstraß (2020): Leonardo-Welten. Zwischen Kunst und Wissenschaft. Weilerswist: Velbrück Wissenschaft; Jürgen Mittelstraß (2021): Fröhliche Wissenschaft? Philosophische Grenzgänge zwischen Wissenschaft und Gesellschaft. Weilerswist: Velbrück Wissenschaft. - Jacke, Christoph (Testcard. Beiträge zur Popgeschichte. Rechtspop.)

Martha and Her Sister(s) – Female Voices in the Fourth Gospel - Taschl-Erber, Andrea (More than Female Disciples: An Examination of Women’s Authority in Ancient Christianity (Ist-VIth centuries))

Making “the Two” Into One Body: De- and Recategorization of (Un-) Circumcision - Taschl-Erber, Andrea (Reconsidering the Letter to the Ephesians in Context (Wissenschaftliche Untersuchungen zum Neuen Testament))

(K)ein Ende des „Alten Bundes“? Paulinische Schrifthermeneutik in 2 Kor 3 - Taschl-Erber, Andrea (Heilige Texte. Verständigungen zwischen Theologie und Kulturwissenschaft)

The influence of effort instructions on fake production costs in basketball novices and experts - Böer, Nils Tobias; Güldenpenning, Iris; Weigelt, Matthias (Abstracts of the 55th Autumn Meeting of Experimental Cognitive Psychology (HExKoP))
Keywords: action preparation; perception; movement planning; deception

Adaptation to context information for head fakes in basketball - Güldenpenning, Iris; Böer, Nils Tobias; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 65th Conference of experimental Psychologists (TeaP))

Wissenschaft und Alltagserfahrung: Überlegungen zur Wissenschaftsdidaktik der Psychologie - Scharlau, Ingrid (Wissenschaftsdidaktik II: Einzelne Disziplinen)
Keywords: Unterrichtsfach Psychologie

Die Nutzung von (Evidenz-)Quellen im Referendariat - Homt, Martina; Bloh, Bea

Private Set Intersection using Third Generation FHE - Anonymous, A.

Rational Models in Cryptography Applied to Matching - Anonymous, A.

Medienästhetik und dann? - Bartz, Christina (Medienkritik und Wirkungsästhetik. Konvergenzen und Zuschreibungen schädlicher und wünschenswerter Rezeptionseffekte von Literatur und Medien seit dem 18. Jahrhundert)

Platform Approach for Modularising Battery Electric fast Ferries - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Anacker, Harald; Dumitrescu, Roman; Papanikolaou, Apostolos (Proceedings of the Design Society)
Abstract The transportation sector is responsible for a relevant share of the total emissions and offers great potentials. It is necessary to implement as many zero-emission mobility systems as possible in the shortest time. For fast ferries, which are a relevant transport manner for a large share of the global population, technical issues could be solved and the successful operation was demonstrated. Up to today high-speed ships have been fully individually designed because physical effects demand for an individual optimisation for each use-case. Specifically for battery electric ships the overall efficiency is crucial to ensure not only an ecological but also economical operation. With today's methods the design and production of such an individual designed ferry does take too long. To cover the rising demand, new approaches for mass production need to be established. In this paper we describe a method for designing a platform for ships with the example of a battery electric fast ferry. The focus is on the actual modularisation, as other aspects like requirements or results of our example case are published elsewhere and are therefore just included briefly. The method is validated on the world's first battery powered high-speed ferry.

A systematic literature review on the Digital Twin of the factory in the context of the product and factory lifecycle - Cieply, Jonas; Disselkamp, Jan-Philipp; Dyck, Florian; Alturk, Waddah; Kühn, Arno; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Development of a modular architecture for complex mechatronic systems - Seidenberg, Tobias; Disselkamp, Jan-Philipp; Jürgenhake, Christoph; Grobbel, Daniel; Dumitrescu, Roman; Papanikolaou, Apostolos (Procedia CIRP)
Keywords: General Medicine

Integrated product and production development - a systematic literature review - Disselkamp, Jan-Philipp; Cieply, Jonas; Dyck, Florian; Grothe, Robin; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systems Engineering Potentials and Use Cases for the Offer Phase in Special Purpose Machinery - Wilke, Daria; Humpert, Lynn; Mansheim, Johanna; Anacker, Harald; Dumitrescu, Roman (DS 125: Proceedings of the 34th Symposium Design for X (DFX2023))

Venture Client Model: A systematic Literature Review - Haarmann, Lennard; Machon, Fabian; Rabe, Martin; Asmar, Laban; Dumitrescu, Roman (European Conference on Innovation and Entrepreneurship)
Established companies are increasingly opening their innovation systems to stay ahead of the competition. In this context, collaboration with innovative and agile start-ups are gaining continuously more importance. In the past established companies often used common corporate venturing methods such as incubators, accelerators, or corporate venture capital for collaboration. Compared to these methods the venture client model is relatively new and was invented by BMW employees in 2014. Using the venture client model, established companies become early clients of the start-ups even it is still a venture to do so. Together they carry out a pilot project to develop a proof of concept and validate it under real conditions. If successful, they enter a long-term collaboration to integrate the start-up’s solution into products, processes, or business models of the established company. The aim of this paper is to sum up the current literature and set a foundation for future research on this topic. Therefore, we conduct a systematic literature review. As a result, we provide a definition of the venture client model, describe characteristics, present advantages from the perspective of established companies and start-ups. In addition, we summarize the state of research regarding strategy, process, and organizational structure and for the venture client model. In terms of strategy, future research should elaborate defining elements of a strategy as well as ways to integrate the venture client model into the corporate innovation-ecosystem. Focusing on the process additional research is needed on a venture client reference process and its integration into the corporate’s core processes. Referring to the organizational structure a reference architecture for a venture client unit as well as its positioning within the organization (e.g., innovation management or corporate strategy) should be further investigated.

Framework for Dual Transformation: A Systematic Literature Review on the Interplays between Digitalization and Sustainability - Kürpick, Christian; Kühn, Arno; Olszewski, Luca; Dumitrescu, Roman (2023 IEEE Conference on Technologies for Sustainability (SusTech))

A Technology Foresight Maturity Model - Ellermann, Kai; Asmar, Laban; Dumitrescu, Roman (ISPIM Conference Proceedings)

A process mining maturity model: Enabling organizations to assess and improve their process mining activities - Brock, Jonathan; Löhr, Bernd; Brennig, Katharina; Seger, Thilo; Bartelheimer, Christian; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (ECIS 2023 Proceedings at AIS Electronic Library (AISeL).)

It’s like flossing your teeth: On the Importance and Challenges of Reproducible Builds for Software Supply Chain Security - Fourné, Marcel; Wermke, Dominik; Enck, William; Fahl, Sascha; Acar, Yasemin (2023 IEEE Symposium on Security and Privacy (SP))

PEA: core-analogue for non-cohesive games - Aslan, Fatma; Duman, Papatya; Trockel, Walter (Economics Bulletin)

Time-resolved pump–probe spectroscopic ellipsometry of cubic GaN. I. Determination of the dielectric function - Baron, Elias; Goldhahn, Rüdiger; Espinoza, Shirly; Zahradník, Martin; Rebarz, Mateusz; Andreasson, Jakob; Deppe, Michael; As, Donat Josef; Feneberg, Martin (Journal of Applied Physics)
An ultra-fast change of the absorption onset for zincblende gallium-nitride (zb-GaN) (fundamental bandgap: 3.23 eV) is observed by investigating the imaginary part of the dielectric function using time-dependent femtosecond pump–probe spectroscopic ellipsometry between 2.9 and 3.7 eV. The 266 nm (4.66 eV) pump pulses induce a large electron–hole pair concentration up to 4×1020cm−3, which shift the transition energy between conduction and valence bands due to many-body effects up to ≈500 meV. Here, the absorption onset increases due to band filling while the bandgap renormalization at the same time decreases the bandgap. Additionally, the absorption of the pump-beam creates a free-carrier profile within the 605 nm zb-GaN layer with high free-carrier concentrations at the surface, and low concentrations at the interface to the substrate. This leads to varying optical properties from the sample surface (high transition energy) to substrate (low transition energy), which are taken into account by grading analysis for an accurate description of the experimental data. For this, a model describing the time- and position-dependent free-carrier concentration is formulated by considering the relaxation, recombination, and diffusion of those carriers. We provide a quantitative analysis of optical experimental data (ellipsometric angles Ψ and Δ) as well as a plot for the time-dependent change of the imaginary part of the dielectric function.
Keywords: General Physics and Astronomy

Frühe Versuche zur Etablierung des Hochschulstandorts Paderborn (1945-1970) - Grüttner, Niclas Christian (50 Jahre Universität Paderborn. Studentische Forschungsprojekte zur Gründungsgeschichte. Ein Rückblick)

Evaluation of the Influence of Different Energy Usage Behavior, Component Dimensionings and PV Orientations on the Suitability and Lifetime of a Hybrid, Hydrogen-Based PV Energy System for a Private Household - Möller, Marius Claus; Krauter, Stefan (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

PV Microinverters: Latest Efficiency Rankings, Energy Yield Assessments, Firmware Issues - Krauter, Stefan; Bendfeld, Jörg (Proceedings of the 40th European Photovoltaik Solar Energy Conference and Exhibition)

Lifelogging in einer Kultur der Digitalität. Analysen aus der medienkompetenztheoretischen Perspektive Dieter Baackes. - Dehmel, Lukas; Burgfeld-Meise, Bianca (Ludwigsburger Beiträge zur Medienpädagogik)

Vibrational Properties of the Potassium Titanyl Phosphate Crystal Family - Neufeld, Sergej; Gerstmann, Uwe; Padberg, Laura; Eigner, Christof; Berth, Gerhard; Silberhorn, Christine; Eng, Lukas M.; Schmidt, Wolf Gero; Rüsing, Michael (Crystals)
The crystal family of potassium titanyl phosphate (KTiOPO4) is a promising material group for applications in quantum and nonlinear optics. The fabrication of low-loss optical waveguides, as well as high-grade periodically poled ferroelectric domain structures, requires a profound understanding of the material properties and crystal structure. In this regard, Raman spectroscopy offers the possibility to study and visualize domain structures, strain, defects, and the local stoichiometry, which are all factors impacting device performance. However, the accurate interpretation of Raman spectra and their changes with respect to extrinsic and intrinsic defects requires a thorough assignment of the Raman modes to their respective crystal features, which to date is only partly conducted based on phenomenological modelling. To address this issue, we calculated the phonon spectra of potassium titanyl phosphate and the related compounds rubidium titanyl phosphate (RbTiOPO4) and potassium titanyl arsenate (KTiOAsO4) based on density functional theory and compared them with experimental data. Overall, this allows us to assign various spectral features to eigenmodes of lattice substructures with improved detail compared to previous assignments. Nevertheless, the analysis also shows that not all features of the spectra can unambigiously be explained yet. A possible explanation might be that defects or long range fields not included in the modeling play a crucial rule for the resulting Raman spectrum. In conclusion, this work provides an improved foundation into the vibrational properties in the KTiOPO4 material family.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Solid solutions of lithium niobate and lithium tantalate: crystal growth and the ferroelectric transition - Bashir, Umar; Böttcher, Klaus; Klimm, Detlef; Ganschow, Steffen; Bernhardt, Felix; Sanna, Simone; Rüsing, Michael; Eng, Lukas M.; Bickermann, Matthias (Ferroelectrics)
Specific heat capacity measurements by differential scanning calorimetry (DSC) of single crystals of solid solutions of LiNbO3 and LiTaO3 are reported and compared with corresponding ab initio calculations, with the aim to investigate the variation of the ferroelectric Curie temperature as a function of composition. For this purpose, single crystals of these solid solutions were grown with Czochralski pulling along the c-axis. Elemental composition of Nb and Ta was investigated using XRF analysis, and small samples with homogeneous and well known composition were used for the DSC measurements. We observed that the ferroelectric Curie temperature decreases linearly with increasing Ta concentration in the LiNb1−x Tax O3 solid solution crystals. Furthermore, the ferroelectric transition width of a mixed crystal appears to be smaller, as compared to pure LiTaO3.
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Learning the pronunciation of segmental features of english phonology at german primary schools - Hahn, Charlotte Anna
In der vorliegenden Arbeit wird die Auswirkung expliziter Ausspracheübungen auf die englische Aussprache von Kindern an Grundschulen in NRW untersucht. Das Ziel dieser Arbeit ist es, eine Alternative für den mittel-offenen vorderen Vokal /æ/ und die dentalen Frikative /, ð/ zu bieten. Es wurde eine Interventionsstudie mit 72 Teilnehmenden aus drei verschiedenen Grundschulklassen durchgeführt; zwei vierte Klassen mit verschiedenen Lehrkräften und eine dritte Klasse, die von der Lehrperson einer der vierten Klassen unterrichtet wurde. Jede Klasse wurde in eine Kontroll- und zwei Interventionsgruppen (je eine für den Vokal und die Konsonanten) geteilt. Alle Gruppen wurden einmal zu Beginn und zwei Mal am Ende der Studie getestet. Zwischen den letzten beiden Tests lagen sechs bis acht Wochen, um einen mittelfristigen Effekt zu testen. Die Intervention, die nach der ersten Messung stattfand, wurde auf zwei je ca. drei-minütige Einzelsitzungen aufgeteilt. Während der Intervention übten die Teilnehmenden mit der Autorin die Aussprache des relevanten Phonems. Die Ergebnisse dieser Studie zeigen, dass die Interventionen einen Effekt auf die Aussprache der Teilnehmenden hatten. Wie sich dieser Effekt verhält und entwickelt scheint von der Art des Phonems, dem Alter der Teilnehmenden sowie der bisherigen Ausspracheschulung abzuhängen. Die vorliegenden Ergebnisse liefern Erkenntnisse nicht nur für die Grundschule selbst, sondern auch für die Lehrer*innenausbildung und Lehrplanentwicklung.

Vorzeichenrichtige tomographische Rekonstruktion von Ultraschallfeldern mit Hilfe der Schlierentechnik - Hetkämper, Tim; Claes, Leander; Henning, Bernd (tm - Technisches Messen)
Keywords: Electrical and Electronic Engineering; Instrumentation

Systematics for an Integrative Modelling of Product and Production System - Schäfer, Louis; Günther, Matthias; Martin, Alex; Lüpfert, Mariella; Mandel, Constantin; Rapp, Simon; Lanza, Gisela; Anacker, Harald; Albers, Albert; Köchling, Daniel (Procedia CIRP)
Keywords: General Medicine

Virtual Assembly for Engineering – A Systematic Literature Review - Dyck, Florian; Anacker, Harald; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Reibungsinduzierter Prozess zum nutzerindividuellen und energieeffizienten Recycling von Aluminiumschrotten - Borgert, Thomas
Die weltweit erzeugten Emissionen müssen in allen emittierenden Sektoren signifikant gesenkt werden, um die Auswirkungen des Klimawandels zu reduzieren. Dies ist unter anderem durch die energieeffiziente Wiederverwertung vorhandener Ressourcen und damit der Einstellung einer nachhaltigen Kreislaufwirtschaft möglich. Aufgrund der hohen erforderlichen Energiemenge in der primären Herstellung von Aluminium existieren hier im Vergleich zu anderen Konstruktionswerkstoffen große Einsparpotentiale. Mit dem in dieser Arbeit erforschten reibungsinduzierten Recyclingverfahren (RIR) wird eine alternative und energieeffiziente Prozessroute zum direkten Recycling von unterschiedlichen Aluminiumschrotten geschaffen. Zur Charakterisierung der Prozessroute werden u. a. die Erkenntnisse aus sich gegenseitig unterstützenden experimentellen und theoretischen Untersuchungen zu den Vorgängen der der Verdichtung, Plastifizierung als auch Extrusion der recycelten Profile dargelegt. Die Einflüsse unterschiedlicher Eingangsgrößen wie z. B. der Werkzeuggestaltung oder der Verarbeitung unterschiedlicher Legierungen werden zudem zur zukünftigen Auslegung des Prozesses erläutert. Aus der abschließenden energetischen Bilanzierung kann geschlossen werden, dass aufgrund der geringeren Verarbeitungstemperatur signifikante Energieersparnisse bei Verwendung des RIR im Vergleich zu den konventionellen Produktionsstrategien erzielt werden können.

Kinderladenbewegung: Auf den Spuren von Kinderladenkindern und ihren Eltern zwischen Laden, Garten und Natur. - Göddertz, Nina; Bock, Karin (Handbuch Kindheit, Ökologie, Nachhaltigkeit)

Kindermädchen – Von ‚strebsamen Mädchen‘, fliegenden Regenschirmen und neuen Gewändern eines (nicht) ausgestorbenen Berufes - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Dienstmädchen – von romantisierten Zuschreibungen und menschenunwürdigen Arbeits- und Lebensbedingungen, damals wie heute. - Göddertz, Nina (Soziale Frauenberufe in Ost und West)

Ein ‚bunter Blumenstrauß‘ an Praxisphasen. Gestaltungsaufgaben und Entwicklungsbedarfe in der Lehrer*innenbildung Sozialpädagogik. - Göddertz, Nina; Schmoekel, Michelle Jaquelina (Berufsbildung. Zeitschrift für Theorie-Praxis-Dialog)

The Choice of Ideology and Everyday Decisions - Burs, Carina; Gries, Thomas; Müller, Veronika (Journal of Organizational Psychology)
Individuals strive to make decisions that are consistent with not only their consumer preferences but also their psychological needs. However, they are confronted with complex, ambiguous or even false information. Ideologies and belief systems provide guidance when processing and evaluating information and give a coherent and comprehensible interpretation of reality. The first question is: why is an individual attracted to a particular ideology? Individuals choose ideologies that resonate with their subjective psychological needs and preferences. Second, how do individuals search for ideologies and find out which suit them best? We model an individual’s sequential information search for the best matching ideologies by applying Bayesian learning and utility optimization. Additional information enhances utility by reducing uncertainty. As a search is costly, the process may stop once an individual adopts an ideology even if the information set remains incomplete. Third, once they have chosen a particular ideology, individuals adhere to its rules and norms when making everyday decisions. Consumers not only physically consume, but they also act in accordance with their psychological needs.
Keywords: Economics; Ideology; Decision-making

Erlebnisorientiert Lehren und Lernen in der beruflichen Bildung. Entwicklung eines didaktischen Konzepts im Rahmen von designbasierter Forschung. - Volgmann, Simone

Minisymposium Data Science - Podworny, Susanne; Frischemeier, Daniel (Beiträge zum Mathematikunterricht 2022: 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik vom 29.08.2022 bis 02.09.2022 in Frankfurt am Main)

Wege zu einer Didaktik der Sozialpädagogik
Wie kann sozialpädagogisches Handeln erlernt und gelehrt werden? Die Qualifizierungswege für sozialpädagogische Fachkräfte sind vielfältig, mitunter widersprüchlich und in verschiedenen Ebenen eingelagert, von Berufsfachschulen, Fachschulen, Fachhochschulen bis hin zu universitären Studiengängen. Ebenso vielfältig sind die beruflichen Anforderungen an sozialpädagogische Fachkräfte. Der Sammelband widmet sich den unterschiedlichen Zugängen zu einer Didaktik der Sozialpädagogik in Bezug auf die Bildungs-, Lern- und Qualifizierungsprozesse zukünftiger sozialpädagogischer Fachkräfte sowie Lehramtsstudierender mit der beruflichen Fachrichtung Sozialpädagogik.
Keywords: Ausbildung Kita-Fachkraft; Ausbildung Soziale Arbeit; Care-Berufe; didaktische Grundlagen; Erzieher*innen-Ausbildung; Erzieher-Ausbildung; Fachkräftemangel; Fachrichtung Sozialpädagogik; Lehramt Sozialpädagogik; schulische Ausbildung; soziale Berufe; Sozialpädagogik unterrichten; Sozialpädagogische Ausbildungsgänge; Sozialwesen; Unterricht Soziale Arbeit

A Social Network Approach for Investigating Social Influences on Effective Use: Demonstration in Virtual Reality Collaboration - Tölle, Laura; Slawinski, Elena; Fromm, Jennifer; Mirbabaie, Milad

Under Pressure? - The Effect of Conversational Agents on Task Pressure and Social Relatedness in Digital Labor - Lichtenberg, Sascha; Hildebrandt, Fabian; Mirbabaie, Milad

Understanding Digital Nomadism as an Employer Branding Signal - Marx, Julian; Langer, Marie; Mirbabaie, Milad